ANALYSIS OF INTER-REGENCY DEVELOPMENT INEQUALITY IN D.I YOGYAKARTA PROVINCE - seno budhi ajar (GeoEco, 2019)
Economic development essentially aims to improve society so that economic growth can be increased and evenly distributed. The problem is that the different growth rates between regions cause a hierarchy and scale of interaction between different regions. This study wants to show the extent to which development inequality follows the existence of a Decentralization system. To explain the spread of economic inequality, the research method used the analysis of the Wililiamson index, Location Quotion Analisis, the analysis of typology klassen. The results of the study, there are economic inequalities between regencies in the Special Province of Yogyakarta.